Religion, education, and governance in the Middle East between tradition and modernity - Krishna-Hensel, Sai Felicia (Global interdisciplinary studies series, 2012)
This interdisciplinary book explores the historical and contemporary role of religious tradition and education on political elites and governing agencies in several major states as well as generally in the region.